Study Of Aerodynamic Performances Of Gliders Using Computational Fluid Dynamics Analysis - Mustapa, Nabila (Universiti Sains Malaysia, 2019)
Developments in geometry modelling, surface and volume grid generation and flow simulation algorithms provide a route to accurate flow field predictions for increasingly complex and realistic format. Hence, computational aerodynamics has appeared as a crucial enabling technology for the design and development of flight vehicles (Slater, 2008). A glider named as UCC-14 is selected to be computationally analysed on their aerodynamics performance specifically lift and drag coefficients. The models are varied in terms of types of airfoil and wing planform which include straight with dihedral tip, elliptical and tapered with dihedral tip. A hand-launched glider is a free flight aircraft that is supported in flight by the dynamic reaction of the air against its lifting surface and not depending on engine. The thrust is fully depended on the force generated by the launcher. Aircraft wings are the lifting surfaces with a specific airfoil sections (Haque et al., 2015). The performance of an aircraft as well as the efficiency mostly depends on the aerodynamic characteristics lift, drag, lift to drag ratio of wings. The effects of wing shapes are very crucial to the aircraft aerodynamic performance (Haque et al., 2015) in terms of the lift and drag distributions along the wing span. The aerodynamic properties of a glider aircraft depend on their shape, imposing significant design constraints (Fukusato et al., 2018). One of the important design phases of an aerodynamically efficient wing is the selection of an appropriate airfoil. The airfoil v selection of a wing design firstly requires performing aerodynamic performance analyses of different airfoils for the purpose of the design (Fukusato et al., 2018). Conventional hand-launched gliders commonly fly at low altitude and low velocity. In this project, the flow is assumed to be laminar at steady state (gliding phase) with incompressible flow. Since the gliding altitude does not exceed 10 meters, the boundary condition which includes inlet and outlet pressure, temperature, and density can be assumed to be the same as at sea-level. A Reynolds number range of 60,400 is specified as the flow properties based on the reference from the journal “Summary of Low-Speed Airfoil Data”. The gliders dimensionS are measured manually and drawn into a computer-aided-drawing CAD software (CATIAV5) as a 3 dimensional geometry. A 2-dimensional analysis is done on RG-14, AG-37 and MH-32 airfoil. All models are simulated and computationally analysed. Comparison of the results on lift and drag coefficient of the models are made to differentiate the aerodynamic effectiveness of each design. The computational results will be compared with the wind tunnel experiment data to obtain the validation of the simulation.